Comparison of Brain Development in Sow-Reared and Artificially Reared Piglets - Jacob, Reeba M.; Mudd, Austin T.; Alexander, Lindsey S.; Lai, Chron-Si; Dilger, Ryan N. (Frontiers in Pediatrics, 2016)
Introduction Provision of adequate nutrients is critical for proper growth and development of the neonate, yet the impact of breastfeeding versus formula feeding on neural maturation has yet to be fully determined. Using the piglet as a model for the human infant, our objective was to compare neurodevelopment of piglets that were either sow-reared or reared in an artificial setting. Methods Over a 25-d feeding study, piglets (1.5 ± 0.2 kg initial bodyweight) were either sow-reared (SR; n = 10) with ad libitum intake, or artificially-reared (AR; n = 29) receiving an infant formula modified to mimic the nutritional profile and intake pattern of sow’s milk. At study conclusion, piglets were subjected to a standardized set of magnetic resonance imaging (MRI) procedures to quantify structure and composition of the brain. Results Diffusion tensor imaging, an MRI sequence that characterizes brain microstructure, revealed that SR piglets had greater (P < 0.05) average whole-brain fractional anisotropy, and lower (P < 0.05) mean and radial and axial diffusivity values compared with AR piglets, suggesting differences in white matter organization. Voxel-based morphometric analysis, a measure of white and gray matter volumes concentrations, revealed differences (P < 0.05) in bilateral development of gray matter clusters in the cortical brain regions of the AR piglets compared with SR piglets. Region of interest (ROI) analysis revealed larger (P < 0.05) whole brain volumes in SR animals compared with AR, and subcortical regions to be larger (P < 0.05) as a percentage of whole-brain volume in AR piglets compared with SR animals. Quantification of brain metabolites using magnetic resonance spectroscopy revealed SR piglets had higher (P < 0.05) concentrations of myo-inositol, glycerophosphocholine + phosphocholine, and creatine + phosphocreatine compared with AR piglets. However, glutamate + glutamine levels were higher (P < 0.05) in AR piglets when compared with SR animals. Conclusion Overall, increases in brain metabolite concentrations, coupled with greater FA values in white matter tracts and volume differences in gray matter of specific brain regions, suggest differences in myelin development and cell proliferation in SR vs. AR piglets.